A comparability study of natural and deglycosylated PD-L1 levels in lung cancer: evidence from immunohistochemical analysis - Mei, Jie (Mol Cancer, 2021)
Emerging evidence has revealed that the removal of N-linked glycosylation could enhance PD-L1 detection. However, whether PD-L1 antibodies against different epitopes of PD-L1 antigens responding to deglycosylation has not been characterized. In this study, we compared natural and deglycosylated PD-L1 expression in lung cancer (LuCa) using a panel of PD-L1 antibodies (28–8, CAL10, 73–10 and SP142). We found that removal of N-linked glycosylation markedly enhanced PD-L1 detection when the 28–8, CAL10 and SP142 monoclonal antibodies (mAbs) were used but slightly inhibited PD-L1 detection when the 73–10 mAb was used. Moreover, for the CAL10 and SP142 mAbs, deglycosylated PD-L1 levels showed stronger correlations with the response to anti-PD-1 therapy. Overall, our research provides a comprehensive insight into the application of deglycosylated PD-L1 detection, which expands the clinical significance of this established strategy in LuCa. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12943-020-01304-4.